Elevated echocardiographic markers for left atrial stiffness and fibrosis in patients with paroxysmal atrial fibrillation. (8th February 2021) - Bastos, L; Al-Khalili, F; Back, M; Manouras, A; Engdahl, J; Shahgaldi, K
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Danderyds Hospital Background: Atrial fibrillation (AF) is associated with atrial disease expressing left atrial (LA) structural remodeling with increased fibrosis and stiffness. Transthoracic echocardiography (TTE) is the first imaging modality of choice for the evaluation of LA volume index (LAVI) and function. However TTE allows new approaches for LA anatomical and functional analysis such as LA stiffness index (LASI) calculation based on LA global longitudinal strain (GLS), LA activation time and LA Integrated Backscatter (IBS). LA activation time is a novel parameter, considered as an echocardiographic surrogate analysis for LA fibrosis. Echocardiographic derived IBS can noninvasively quantify myocardial fibrosis in the left ventricle, allowing a similar alternative analysis for LA fibrosis. Purpose: To investigate potential LA structural and functional changes in paroxysmal AF patients by measuring LA activation time, LASI and LA IBS compared with age-matched control group. Methods: In total, 75 paroxysmal AF patients and 99 age-matched control group patients (mean age 77 ± 0.4) were enrolled from STROKESTOP2 study. Patients with paroxysmal AF were included from a subgroup of newly screened-diagnosed AF. TTE examinations were analyzed retrospectively offline using dedicated software. NTproBNP levels ( ≤ 900 ng/L) was an enrollment criterium. LA activation time was acquired by measuring the time delay between the onset of the P-wave on ECG and the peak of the Á –wave on the Tissue Doppler (TD) tracing in the lateral LA wall. LASI was calculated as the ratio of E/é to LA-GLS. LA IBS was obtained as the intensity difference between the LA lateral wall and the pericardium, at QRS peak. Results: There was a significant increase of LASI (0.53 ± 0.21 vs. 0.41 ± 0.22, P < 0.05) and LA IBS (14 ± 7.1 dB vs. 11 ± 6.3 dB, P < 0.05) in the AF group compared to the control group. Feasibility for LASI resulted as 64 %, respectively 91 % for LA IBS. LA activation time was significantly prolonged in the AF group (157 ± 34 ms vs. 134 ± 18 ms, P < 0.05) with a feasibility of 44 %. In the AF group, 45 patients (60 %) expressed normal LAVI <34 ml/m2. No significant difference was revealed concerning LAVI (P > 0.05) between the groups (AF group with normal LAVI). Although LASI, LA IBS and LA activation time remained significant increased in the AF group (P < 0.05). No significant difference was shown regarding NT-proBNP levels. (P > 0.05) between the AF group 243 (179-420) ng/L and the control group 219 (160-317) ng/L. Conclusions: Indices reflecting LA stiffness and echocardiographic parameters associated with LA fibrosis, were elevated in patients with paroxysmal AF compared to age-matched controls. These findigs might non-invasively provide additional information in paroxysmal AF patients with normal LA size.